Layered double hydroxides for removing and recovering phosphate: Recent advances and future directions - Keyikoglu, Ramazan; Khataee, Alireza; Yoon, Yeojoon (Elsevier, 2022)
Eutrophication is a widespread environmental challenge caused by excessive phosphate. Thus, wastewater engineers primarily aim to limit the phosphate concentration in water bodies. Layered double hydroxides (LDHs) are lamellar inorganic materials containing tunable brucite-like structures. This review discusses the fundamental aspects and latest developments in phosphate removal using LDH-based materials. Based on the divalent cations, Ca, Mg, and Zn-containing LDHs are largely used along with trivalent cations such as Al and Fe owing to their limited toxicities. However, classical LDHs are affected by the presence of co-existing anions, have a narrow working pH range, and have moderate adsorption capacities. Binary LDHs have been designed to be selective towards phosphate by the addition of a third metal such as Zr4+. Developing LDH composites with magnetic, polymeric or carbon materials are feasible approaches for increasing adsorption capacity, stability, and reusability of LDHs. Biochar as a carrier material for LDHs achieved remarkable phosphate adsorption performance and improved LDH dispersion, anion exchange capacity, and ease of separation. The use of recovered phosphate as an SRF, which is a type of bioavailable fertilizer, is a promising approach.
Keywords: Layered nanomaterials; Phosphate species; Phosphate recovery; Carbon composites; Adsorption